The differential mediating roles of ideal and ought-to L2 writing selves between growth mindsets and self-regulated writing strategies. (November 2022) - Xu, Jian; Wang, Yabing
Abstract: Despite the important role growth mindsets play in second/foreign language (L2) writing, insight into its influence on motivation and strategy use in L2 writing contexts has been limited. To address this research gap, the present study explored the relationship between growth mindsets, ideal and ought-to L2 writing selves, and the use of environmental, behavioral, and personal self-regulated learning (SRL) writing strategies, particularly how ideal and ought-to L2 writing selves mediated the relationship between growth mindsets and three SRL writing strategies. Three hundred and sixty-two English-as-a-foreign-language (EFL) undergraduates completed the questionnaires. Structural equation modeling was used to analyze the data. The results on the direct effect showed that growth mindsets positively predicted ideal and ought-to L2 writing selves, and three SRL writing strategies; the ideal L2 writing self, rather than the ought-to L2 writing self, positively predicted the use of three SRL writing strategies. The results on the indirect effect revealed that the ideal L2 writing self mediated the relationship between growth mindsets and three SRL writing strategies, whereas the ought-to L2 writing self did not. Implications for L2 writing instruction in a tertiary context are discussed.